Validation of MINAPAMIMI fairy tale media to improve elementary school students knowledge and attitudes towards distater mitigation - Angelia, Inge; Handayani, Sri; Raid, Naufal; Elsa Fitri, Wiya (Universitas Ahmad Dahlan, 2024)
The high risk of earthquakes and tsunamis in several regions of Indonesia, with the majority of victims being children due to a lack of disaster mitigation knowledge and the scarcity of disaster mitigation learning media. This research aims to determine the validity level of the MINAPAMIMI Fairy Tale Book in enhancing the knowledge and attitudes of elementary school students. This study addresses the limitations of learning media for schools in improving earthquake and tsunami disaster mitigation among elementary school students. The subjects of this research are elementary school students in Padang City, utilizing the Research and Development (R&D) method with the IDI design model. Data collection is conducted through questionnaires and analyzed descriptively based on validation score sheets; the product is validated by three experts. The validity results will be tested using the Aiken V formula. The research findings indicate that the MINAPAMIMI Fairy Tale Book is deemed valid with an average Aiken V score of 0.82 and can be utilized to enhance the knowledge and attitudes of disaster mitigation among elementary school students. Therefore, it is recommended for elementary schools in earthquake and tsunami-prone areas to utilize the MINAPAMIMI Fairy Tale Book for enhancing disaster mitigation.